La formación docente y su incidencia en el proceso de aprendizaje de los estudiantes de la ue Adolfo María Astudillo, Babahoyo, 2021 - Urresto Santillan, Rosa Angelline (2021)
The present research work called "TEACHER TRAINING AND ITS IMPACT ON THE LEARNING PROCESS OF EU STUDENTS ADOLFO MARIA ASTUDILLO, BABAHOYO, 2021" which has been developed in order to determine how teacher training affects in the learning process of EU students Adolfo María Astudillo, Babahoyo, 2021. Descriptive research and causal research were applied, the survey was used as a tool, which was directed to 30 students from the aforementioned educational institution, the results obtained allowed us to identify the variables involved in the hypothesis. Once the survey was carried out, which consisted of 20 questions, we were able to identify the characteristics and shortcomings that influence the learning process of students, concluding that there is a low level of knowledge about the use of technological tools by the teacher, which It has repercussions at the time of teaching their class, as this limits them to developing attractive and dynamic classes, where the student can function and interact effectively in the activities that the teacher proposes. In this context, we can verify that teacher training is significant for the teaching-learning process of students.